Organizational Culture and Staff Welfare as Correlates of Job Involvement Among University Employees in Ogun State - Uwannah, Ngozi Caroline; Familusi, Kehinde Elizabeth (Advances in Social Sciences Research Journal, 2023)
Human beings are important asset whose services are germane if an organization is to achieve high level of productivity hence this study investigated the relationship between organizational culture, staff welfare and job involvement among university employees in Ogun State. A survey research design was adopted and simple random sampling technique was employed to select 345 employees that participated in the study. A self-structured questionnaire with Cronbach alpha of r = 0.820 tagged “organizational culture, staff welfare and job involvement scale” was administered to elicit information from the participants. Pearson Product Moment Correlation analysis was used to test the stated hypotheses at 0.05 level of significance. Findings from the study revealed significant negative relationship between organizational culture and job involvement (r = -.122, p < .05), no significant relationship between staff welfare and job involvement (r = -.102, p > .05), and significant relationship between organizational culture and staff welfare (r = .804, p < .05). Based on the findings, the researchers, concluded that the major factors that could improve the employee job involvement in every organization are organizational culture and staff welfare, hence, it was recommended that university management should review their policies on organizational culture to make it employee accommodating while effort should be made to ensure that policies on staff welfare should be reviewed consistently to meet the personal needs of the workers.